2013
DOI: 10.1007/s00595-013-0550-4
|View full text |Cite
|
Sign up to set email alerts
|

Lichtenstein repair of indirect inguinal hernias with acellular tissue matrix grafts in adolescent patients: a prospective, randomized, controlled trial

Abstract: Lichtenstein hernioplasty using ACTM grafts has comparable safety and efficacy to traditional high ligation of the indirect hernia sac in adolescent patients. ACTM can reduce the incidence of recurrence in adolescents with Gilbert type 3 hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…A prospective trial performed comparing adolescent high ligation repair with a Lichtenstein hernioplasty using acellular tissue matrix mesh repair demonstrates longer operative times with mesh repair, but no significant difference was found in recurrence rate with a follow-up of 30 months. 6 However, the reverse principles of applying pediatric surgical methods to adults have not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective trial performed comparing adolescent high ligation repair with a Lichtenstein hernioplasty using acellular tissue matrix mesh repair demonstrates longer operative times with mesh repair, but no significant difference was found in recurrence rate with a follow-up of 30 months. 6 However, the reverse principles of applying pediatric surgical methods to adults have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Postpubertal adolescents have similar anatomy to the adult population with a larger internal inguinal ring diameter and variations on transverse fascia defects. 6 Inguinal hernia repair in adults is also the most commonly performed surgical procedure for an adult general surgeon. 7 However, adult herniorrhaphy is most often performed with mesh placement because of concerns that high ligation alone would have a higher recurrence rate.…”
mentioning
confidence: 99%
“…et al[18] have done a comparative study of the high ligation of the laparoscopic hernia sac and the posterior wall repair in the adolescent indirect hernia. The size of the internal ring diameter in the two groups was 2.37 ± 0.52 (1.60-3.62) cm VS 2.41 ± 0.58 (1.59-3.65) cm (p = 0.592).The results showed that the recurrence rate in high ligation group(4/115,3.48%) was higher than that in posterior wall suture repair group (0/129,0%) (p = 0.048).Shen Yingmo et al [22]have done a prospective comparative study between high ligation and Lichtenstein hernioplasty using acellular tissue matrix (ACTM) grafts in adolescent patients. the diameter of the two groups was 2.2 ± 0.5cm vs2.3 ± 0.5cm(p = 0.499) ,The results showed that the recurrence rate no difference between the two groups6% (3/50) vs0% (0 / 50) (p = 0.079), but subgroup (the patients with Gilbert type 3 hernias)analysis found that the recurrence rate of high ligation group was higher than mesh repair group.…”
Section: Discussionmentioning
confidence: 92%
“…From the current literature [18,22],the conclusion seems to be drawn. the diameter of internal ring more than 3cm or severe transverse fascia defect of adolescent indirect hernias were recommended to use mesh repair, when the diameter of internal ring between 2-3cm ,the e cacy of high hernia sac ligation was controversial, these patients can be considered laparoscopic posterior wall suture repair or open muscle repair.…”
Section: Discussionmentioning
confidence: 94%
“…According to the results of our clinical study [18], the authors found that the simple high hernia sac ligation is inadequate for adolescents (13 to 18 years old) with a longer medical history, larger diameter of internal inguinal ring, and more serious transverse fascia defects. The inguinal hernia treated with simple high hernia sac ligation in adolescents is prone to postoperative recurrence; therefore, the procedure, similar to the treatment of adult inguinal hernia, should be taken, for example, repairing the transverse fascia and strengthening of the posterior wall of the inguinal canal.…”
Section: Indications For Surgerymentioning
confidence: 99%